Consumption Demand For Selected Food Commodities In Saudi Arabia With Projections For 1993 - Mohamad, Abdul-Ghani Mohammed Abdul-Qadir (Kansas State University, 1988)
The main objective of economic planning in most lessdeveloped countries is to achieve a higher standard of living through more employment, higher production, and increases in per capita real income. A rise in per capita real income usually triggers an increase in demand for different food and nonfood commodities. This was especially true for Saudi Arabia in the past decade. As its petroleum export earnings bounded upward to $100 billion in 1980, Saudi Arabia gained prominence as an agricultural importer.